The difficult adaptation to changes: the Church, Falange and the Spanish society during the “Second Francoism” (1960-1975) - Hernández Burgos, Claudio (Hispania Nova, 2019)
This article analyses the process of adaptation of both the regime and the society to the deep transformations which characterized the so called ‘Second Francoism’. To do that, relying on different archival sources, newspapers and relevant literature, this research uses a perspective focused on the provinces to assess both the real scope of Francoist projects to survive and the changing attitudes and behaviour of Spaniards. Sections one and two explores the ability of National-Catholic and Falangist political cultures to adapt themselves to a new environment. Finally, the article explores the Spanish society’s heterogeneous and contradictory responses towards the regime’s discourses and policies. This research aims to provide a deeper and more complex understanding of the relationship between State and people during the last years of Francoist dictatorship.